Analysis and Forecast of Coupling Coordination Between Theme Park and Urban Development: A Case Study of Fante Theme Park in Wuhu. Issue 4 (March 2019) - Li, Deming; Zhu, Guoxing; Yu, Xiangyang; Zhang, Junxiang
Abstract: The construction and development of theme parks play an important role in promoting urban economy, society and environment. At the same time, the city also plays a supporting and safeguarding role in the construction and management of theme parks. Based on the discussion of the interaction mechanism between theme parks and urban development, this paper takes Fante theme park in Wuhu as an example to analyze the development level of the city and the coupling coordination degree of theme parks, in which the Entropy method and the coupling model are applied. GM (1.1) forecasting model is also used in hope of predicting the coupling coordinative degree of Fante theme park and Wuhu city in the next five years. The results show that the development level of Fante theme park and Wuhu city keeps increasing despite a slight fluctuation. The coupling coordinative degree presented a steady upward trend, with the coupling level rising from low coordination in 2008 to an antagonism stage, a comparatively moderate coordination in 2015. Therefore it is safe to say that in the next few years, the coupling coordinative degree of Fange theme park and Wuhu city will be significantly improved. The rising of coupling level and the evolution of coordination degree will be kept at the same pace. However, there is still a long way to go before the coupling coordination level of the two to develop to higher stage.